ANALISA AKUNTABILITAS DAN TRANSPARANSI TENTANG IMPLEMENTASI KEBIJAKAN PENGELOLAAN BOS - Hariswati, Nurul (Faculty of Economics and Business, University of Muhammadiyah Malang, 2015)
This research was conducted with the aim to analyse the implementation of the accountability and transparency financial management which the source stemming from government. The approach used is a case study of indepth interview from financial manager, head master, and stakeholders. The results of this research show that first appeared as constraints and not regulated and obligations of private schools in terms of taxation. Second, the scale of priority importance of accountability between the financial manager and head master has different values so as conflicts of interest. Third, the implementation of transparency development from the publication such as via the website, call center, facebook. The fourth, the Government has n ot set a standard policy to use of the grant allocations.